Sprit Pluralisme Dalam Konstruktur Karakter Bangsa Indonesia (Sebuah Pendekatan Sosio-Historis Pada Konsep Nation State) - Aan Hasanah (Al-Risalah, 2011)
The aim of this article is to discuss the pluralism values in building the nation characters. Indonesia consist of prular ethnis, nation, and religions that if its pluralisme is not well-maintained there will be secial conflict, even worse violence which result in many victims. Recent conflicts happen on behalf of communities, ethnic and even religion. To solve that problem, the nationcharacharecter neds to be built in order to creat a high-civilized, cooperative and peaceful nation. The nation-charchter can be build by the sprit of pluralism that is building the multi=cultural Indonesian into reak Indonesia who understand their position to build peaceful in Indonesia, the nation-character building is applied in two forms: autonomy and heteronomy that is the building from internal and esternal (anvironment) aspects.